The Post Cold War Order in Asia and the Challenge to ASEAN - Yahuda, Michael (Book collections on Project MUSE., 2006)
This paper was delivered by Professor Michael Yahuda, Elliott School for International Affairs, George Washington University, at the Fourth Asia and Pacific Lecture organized by the Institute of Southeast Asian Studiesin Singapore on 24 August 2005 ...